Computer-Based Nursing Care Intervention Information System Design - Emilia Puspitasari Puspitasari; Mulyono Mulyono (Indonesian Journal of Global Health Research, 2022)
The development of a nursing care documentation system is based on making it easier for nurses to do their jobs. The documentation system developed is expected to be able to predict clearly and accurately, besides that the system must be efficient both in terms of saving time, facilitating the work of nurses. There needs to be the development of a nursing information system that can be used in educational institutions that are expected to be able to facilitate the student learning process in accordance with the needs of the field of nursing clinical practice. The purpose of this study is to design a computer-based nursing intervention documentation system. The method used is to use several stages of activity including System Requirements Analysis, Database Planning, Application Planning, and User Interface Design. The results obtained are the design of an information system for nursing intervention documentation for students. The recommendation of this research is that the design of nursing care interventions can be applied in nursing learning.